Demographic characteristics of companion animals identified with electronic devices in two districts of Lima - Peru - Gil, Angie (2022)
The aim of this study was to describe the demographic characteristics of companion animals (canines and felines) identified with electronic devices in the districts of Lince and San Borja, Lima-Peru, in the period 2013-2021. The descriptive observational study collected information from district, species, sex, breed, size, date of birth, reproductive condition, address, and vaccination programme of the animals identified with electronic devices registered in the database of the National Registry of Animal Identity (RENIAN). Information was retrieved from 782 animals. Of them, 24% were from the district of Lince and 76% of San Borja; whereas 83.5% were dogs and 16.5% felines. The highest proportion of dogs was identified and registered in 2019 (74.4%) and felines in 2021 (63.4%). The number of animals registered in relation to the estimated population of dogs and cats was <5%. The age updated to February 22, 2022, was 5.5 ± 0.2 years in canines and 3.8 ± 0.5 years in felines. Male animals prevailed among dogs (56.1%) and felines (55.8%); as well as purebred (66.1%) among dogs and mestizo (82.2%) among felines. Besides, 21% of the dogs and 63.6% of the felines were sterilized. The vaccination record was outdated. The practice of identifying companion animals based on electronic devices in the districts of Lince and San Borja is scarce, so knowledge of demographic and epidemiological patterns is limited, affecting potential interventions of interest in public health.